Construction of Attitude Towards Punctuality Scale for University Students and Relationships to CSE and FTP - Bhanthumnavina, Duangduen; Bhanthumnavinb, Duchduen; Sorodc, Bung-On (International Journal of Engineering and Technology, 2018)
Time is essential in the modern industrial-technology society. In order to enhance time management skills in university students, Attitude toward punctuality Scale (ATP) was constructed. There were four studies with the total sample of 1,325 university students in Thailand. Eighty-three items were constructed, but only 36 items were selected by a group of experts. A six rating scale accompanied each of the item, ranging from 1 â€œnot true at allâ€ to 6 â€œextremely trueâ€.Â In study1 with 200 students, 31 out of 36 items met the criteria for item quality.Â Results from EFA in study 2 using new 500 students revealed a three-factor model (5 items for cognitive aspect, 4 items for behavioral intention aspect, and 3 items for affective aspect) with the total of 12 items and 59.303% of the total variance accounted for. In study 3 using another 300 students, this model was confirmed by CFA. In study 4 using 225 students, it was found that CSE and FTP were positively and significantly related to the newly constructed ATP (r = .357 and .256, respectively). Furthermore, ATP could predict punctual behavior beyond CSE and FTP for 26.500% with the total of 38.40%. The importance of ATP was discussed. Future experimental studies, as well as, possible intervention programs are suggested. Â Â Â Â